2004
DOI: 10.1167/iovs.04-0060
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Aqueous Humor Outflow by Ionic Mechanisms Involved in Trabecular Meshwork Cell Volume Regulation

Abstract: Cell swelling activates a regulatory volume decrease mechanism that implies activation of K(+) and Cl(-) currents and participation of P2Y(2) receptors. Because previous studies have shown that intracellular volume of TM cells is an important determinant of outflow facility, it seems feasible that cell volume regulation would be part of the homeostatic mechanisms of the TM, to regulate the outflow pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 36 publications
(63 reference statements)
6
89
0
Order By: Relevance
“…2 and 3) (Crosson et al, 2004;Soto et al, 2004), bradykinin (Llobet et al, 1999), and carbachol (Shade et al, 1996). Interestingly, drugs that induce large and sustained Ca 2ϩ mobilizations either decrease outflow facility (bradykinin, carbachol, and endothelin-1) (Wiederholt et al, 1995;Llobet et al, 1999) or do not modify it (Up 4 U and ATP; this study and D. Soto and X. Gasull, unpublished observations).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…2 and 3) (Crosson et al, 2004;Soto et al, 2004), bradykinin (Llobet et al, 1999), and carbachol (Shade et al, 1996). Interestingly, drugs that induce large and sustained Ca 2ϩ mobilizations either decrease outflow facility (bradykinin, carbachol, and endothelin-1) (Wiederholt et al, 1995;Llobet et al, 1999) or do not modify it (Up 4 U and ATP; this study and D. Soto and X. Gasull, unpublished observations).…”
Section: Discussionmentioning
confidence: 59%
“…Other mechanisms proposed as playing important roles in TM function include changes in extracellular matrix (Tian et al, 2000), up-regulation/down-regulation of genes (Borras, 2003), and changes in cell shape (Gills et al, 1998) or cell volume (Al-Aswad et al, 1999;Soto et al, 2004). It is possible that dinucleotides could modify some of these parameters such as cell volume, as proposed for other compounds (Fleischhauer et al, 2003;Srinivas et al, 2004).…”
Section: Dinucleotide Effects In Aqueous Humormentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this effect has been linked to the presence of P2Y 1 receptors in the place when the aqueous humour is drained, the trabecular meshwork [33]. On the other hand, the effect on P2Y 6 has also been described and moreover, it has been suggested that it is connected to a change in the ciliary body blood vessels [29].…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular calcium concentration ([Ca 2+ ] i ) was measured as described in detail previously (Bataller et al, 2001;Soto et al, 2004). Briefly, BV2 cells were plated on 25-mm diameter glass coverslips (VWR Scientific Inc., Philadelphia, PA) and then loaded with 4 µM fura-2/acetoxymethyl ester (Calbiochem, San Diego, CA)…”
Section: Measurement Of Cytosolic-free Ca 2+ and Stimulation Of Vgccmentioning
confidence: 99%